1999
DOI: 10.1021/jo990867j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Nucleophile-Induced Rearrangements of Spiroketones

Abstract: Three tetraketones based on the 2,2'-spirobiindan-1,1',3,3'-tetraone skeleton were prepared and investigated. All three compounds show spiroconjugation between their perpendicular pi-networks. The interaction results in lowering of the energy of the LUMO of the systems by ca. 0.2-0.3 eV as compared to non-spiroconjugated models. The spiroketones are susceptible to nucleophile-induced retro-Claisen condensations that lead to molecular rearrangements destroying spiro connectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…[24] In contrast, no NOE was found upon excitation of the proton at C8 in the E-isomers. [25] The 1 H NMR data (Table 4) correlate with the proposed structures. The proton at C4 of the E-isomer is observed at lower field (for CDCl 3 solution: ca.…”
Section: Resultsmentioning
confidence: 55%
“…[24] In contrast, no NOE was found upon excitation of the proton at C8 in the E-isomers. [25] The 1 H NMR data (Table 4) correlate with the proposed structures. The proton at C4 of the E-isomer is observed at lower field (for CDCl 3 solution: ca.…”
Section: Resultsmentioning
confidence: 55%
“…5 Despite reassuring literature precedents for the analogous simple addition of excess phenyl magnesium bromide reagent to 1,3-indandione, 6 the attempted synthesis of 1 did not proceed as expected. The only product (33% from 2) isolated from the product mixture of the reaction between 2 and the 2-biphenylmagnesium bromide, followed by a work-up in strong acid, gave highly complex 1 H and 13 C NMR spectra despite providing encouraging IR (no band corresponding to C=O stretch) and mass spectra ([M + ] = 254, which could correspond to loss of OH from the anticipated product 1).…”
Section: Resultsmentioning
confidence: 92%
“…Polyphosphoric acid (100 mL) was heated to 80 °C and 2,2-dimethylmalonic acid (5.00 g, 37.8 mmol) and veratrol (4.18 g, 30.3 mmol) were added and the mixture was stirred for 3 h. The reaction mixture was poured into ice water (200 mL). The precipitate was filtered under suction and recrystallized from methanol to give the desired product (2.97 g, 42%) as a white solid, mp 217 -219 °C (224 -226 °C) 5 . 1 H NMR (500 MHz, CDCl 3 ): δ = 7.32 (s, 2H), 4.02 (s, 6H), 1.27 (s, 6H) ppm.…”
Section: Discussionmentioning
confidence: 99%
“…2,2′‐Dibenzyl‐ N , N ′‐bis(8‐quinolyl)malonamide (di‐BenzBQMH 2 ; 1c) and 2,2′‐Bis(2‐phenylethyl)‐ N , N ′‐bis(8‐quinolyl)malonamide (di‐PhEtBQMH 2 ; 1d): The disubstituted ligands 1c and 1d were synthesised according to Hirose et al,14 but the saponification of the malonic esters was carried out as reported by Maslak et al15…”
Section: Methodsmentioning
confidence: 99%